Creche: de lugar de abandono a espaço educativo - Morel, Cristina Maria Toledo Massadar (1991)
This paper presents a historical study of day-care centers in Brazil, analysing how the same institution that bears the stigma of being a place for abandoning children is nowadays understood by some social groups as an educational space. The discussion of private day-care centers is privileged. Working within the framework of a perspective which acknowledges the importance of the social-economic context for the educational proposals, its starting point is a study analysing the relations between the dernand for day-care centers and the female status regarding work and the family, according to some studies about the female condition. Also highlighted are the relationship between the goals which historically were defined for this sort of institutions and the growth of specialized knowledge about the young child, emphasizing the study of the Escola Nova movement. A further stop consists in an analysis of the first magazines which since the 19705 have made accessible the knowledge about child development and helped creating a certain conception of day-care centers. Finally the insertion of the middle class as user of this type of instituion - which emphasizes its educational aspect takes into account the society's modernization process, the growing of women in the labour market and the diffusion of knowledge about young children.